Synthesis and characterization of Ag/TiO2-B nanosquares with high photocatalytic activity under visible light irradiation - Yu, C.; Wei, L.; Li, Xin Yong; Chen, J.; Fan, Q.; Yu, J. (2013)
Square-like B doped TiO2 nanocrystals were first synthesized by a mild solvothermal method with H3BO4 and titanium isopropoxide as the precursors, and isopropyl alcohol as reaction medium. Then, Ag nanoparticles were deposited on TiO2-B nanosquares by photo-deposition. The as-synthesized products have been investigated by photocatalytic reaction test and characterized by powder X-ray diffraction (XRD), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS), and UV-vis diffuse reflectance spectra (DRS). The results showed that boron was successfully doped into TiO2 nanosquares under solvothermal condition. The obtained Ag/TiO2-B composite showed high efficiency in degradation of acid orange II under visible light irradiation. The high photocatalytic performance could be attributed to the synergistic effect of B doping and the plasmon photocatalysis role of the deposited silver nanoparticles over TiO2. © 2013 Elsevier B.V. All rights reserved.